Evaluation of Self-Perceptions of Expectant Mothers - ÖZTÜRK ALTINAYAK, Serap; ÖZKAN, Hava; HÜR, Seçil (Göbeklitepe Medical Science Journal, 2021)
This research was conducted to evaluate the self-perceptions of expectant mothers. This research was conducted in descriptive design. The sample of the research consists of 300 pregnant women who applied to the gynecology outpatient clinics of Lüleburgaz State Hospital between September and December 2018, between 12-40 weeks of gestation. The data were collected using the "Personal Information Form" and the " Self Perception of Pregnants Scale ". Data were evaluated using descriptive statistics, Kruskal Wallis and Mann Whitney U tests. When some demographic characteristics of the pregnant women were examined, it has been determined that the mean age was 27.43±5.41, 35.3% of them were high school graduates, 86.7% lived in a nuclear family, 67% had income equal to expenditure, 93.7% had a planned pregnancy, 69% were in the third trimester of pregnancy, 53% had a positive body image, 80.7% had a positive perception of maternity during pregnancy. When some introductory characteristics of the pregnant women and the Self Perception of Pregnants Scale sub-dimension mean scores were compared, it was found that there was a statistically significant difference between the sub-dimension of the perception of maternity of pregnancy and the state of planned pregnancy, the state of perceiving the body that is changing / will change, and the state of perceiving maternity during pregnancy (p<0.05). It was determined that women's perception of maternity during pregnancy was high, and body perception of pregnancy was negative.